Efforts in raising awareness of corruption among youth: the role of the community and the Malaysian anti-corruption commission (MACC) in enhancing integrity and self-identity - Muhammad Safuan Yusoff; Irma Wani Othman; Mohd Nizam Husen; Muhammad Huzaifah Mohd Kamal (Global Academic Excellence, 2024)
The concept of Corporate Social Responsibility (CSR) has been recognized for a long time and has had a varied history, marked by the development of this fascinating concept over the years. In this conceptual paper, we will focus on factors that shape the understanding and definition of CSR as seen in academic literature and previous scholars' perspectives, and we will highlight how those factors shape the development of the concept of CSR as seen in academic literature. Among these factors are academic contributions, international policies, and significant social and political events. This study employs a comprehensive literature review method to examine the academic contributions that most significantly influence the evolution of CSR processes and concepts. Based on results from the study, it has been proven that corporate responsibility has shifted from a narrow scope to a model in which organizations are able to generate profits, while also being more responsible for enhancing reliability and reputation of their firms. Additionally, social expectations regarding corporate behaviour have evolved, and it is recommended that academic studies related to CSR continue to expand and remain relevant over time.